SECONDARY AORTOENTERIC FISTULA – AN UNCOMMON SOLUTION FOR A COMPLEX CASE - Ferreira, Tiago (2017)
IntroductionSecondary aortoenteric fistula is a fearsome complication of aortic surgery due to its high morbidity and mortality. Therapeutic decision-making is mostly determined by the possibility of concomitant prosthetic infection. Case reportWe present the case of a 55 year old male patient with previous juxta-renal aortic aneurysm resection and tube graft interposition. A left kidney infarction was detected at the third post-operative month during investigation for persistent lumbar pain. The patient was admitted 14 months after the surgery with a four-month history of fever, night sweats and weight loss and. A CT angiogram revealed thickening of peri-aortic tissues and a fluid collection anteriorly to the left iliopsoas muscle. A PET scan showed increased uptake around the graft, indicating the presence of infection. The patient underwent axillobifemoral bypass and removal of the infected graft with ligation of the para-renal aorta. Revascularization of the right kidney was achieved via hepatorenal bypass with inverted great saphenous vein. A fistulous tract in the third portion of the duodenum was noted, mandating duodenectomy and Roux-en-Y gastrojejunostomy. The patient completed a three-week course of triple antibiotic and anti-fungal therapy and a further week of double antibiotic therapy, being discharged after 30 days. A CT angiogram at six weeks showed continued patency of the revascularization procedures and no intra-abdominal complications. ConclusionOpen surgery remains the most effective treatment in good-risk patients. The adoption of alternative solutions is a necessity to cope with the anatomic singularities of more complex cases.